Desenvolvimento de filmes de amido incorporados com cera de abelha por casting contínuo - Luchesi, Bruno Ribeiro (Universidade Federal de São Carlos, 2019)
Starch films appear as an alternative to problematic non-biodegradable plastic films; however, they have low water resistance and require the addition of a hydrophobic component to be viable substitutes for non-biodegradable films. Beeswax is a biodegradable and hydrophobic substance, mostly composed of esters, hydrocarbons and fatty acids. In this context, the objectives of this work were to reduce the interaction of corn starch films with water through the incorporation of different levels of beeswax and evaluate the surface hydrophobicity and the water vapor permeation properties of these films. The films were obtained via continuous casting to establish a pre-pilot processing scenario. The application of continuous casting to obtain the starch/beeswax films resulted in a productivity, at least, 50 times greater compared to the conventional bench casting reported in the literature. Advanced scanning electron microscopy images showed the immiscibility of the beeswax domains and the starch matrix, sufficient to alter the interaction of light with the films, reducing their transparency and clarity and increasing their opacity. In addition, these domains induced the starch matrix to crystallize even with the reduced crystallinity of the wax in the domains. The interaction between the wax and the starch, suggested by ATR-FTIR, directly influenced the properties of the films. The tensile strength was reduced by 39%, the maximum and at break elongation were reduced by 60% and 58%, respectively, while the elastic modulus increased by 327% with the wax content. Finally, the addition of increasing levels of beeswax increased surface hydrophobicity by 100% and reduced the water vapor permeability of the films by 200%, reaching the goal of making them less susceptible to the effect of moisture.
Development of starch films incorporated with bee wax by continuous casting
Keywords: Amido de milho; Cera de abelha; Hidrofobicidade; Casting contínuo; Corn starch; Beeswax; Hydrophobicity; Continuous casting; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS